1977
DOI: 10.3382/ps.0560231
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin Requirement of Starting Chickens in a Tropical Environment

Abstract: Growth rate of broiler chicks tends to be lower in the tropics than in the temperate zone. Results show that up to 17% of dietary riboflavin is destroyed within 24 hours of exposure of the feed to light hence the level of 3.6 mg. of vitamin B2 recommended does not meet the requirement for growth of broilers. Growth study as well as accumulation of riboflavin in meat and organs of the birds showed that increasing levels of dietary riboflavin increases its deposition in meat and organs of the birds. Optimum grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Riboflavin has been reported to be essential in the utilisation of dietary energy and protein (Chou et al, 1971). While birds in the tropics generally consume less feed than those in the temperate regions (Scott et al, 19691, the loss of up to 17% dietary riboflavin within 24 hours of feed exposure (Ogunmodede, 1977) makes it imperative to increase dietary nutrient density to offset deficiency caused by these and other peculiar conditions. The inclusion of higher levels of riboflavin above the recommended level in this study appears to have left enough riboflavin even after losses on exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Riboflavin has been reported to be essential in the utilisation of dietary energy and protein (Chou et al, 1971). While birds in the tropics generally consume less feed than those in the temperate regions (Scott et al, 19691, the loss of up to 17% dietary riboflavin within 24 hours of feed exposure (Ogunmodede, 1977) makes it imperative to increase dietary nutrient density to offset deficiency caused by these and other peculiar conditions. The inclusion of higher levels of riboflavin above the recommended level in this study appears to have left enough riboflavin even after losses on exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Card and Nesheim (1976) reported that riboflavin is most likely to be deficient in poultry feeds. Consequently higher amounts of riboflavin are required by starting chickens (Ogunmodede, 1977) and growing Pullets (Arijeniwa and Ogunmodede, 1995) compared with those in the temperate zone as climatic factors stimulate partial inactivation of the vitamin added to the ration. The objective of this study was to determine the level of riboflavin needed in the diet of hens to ensure optimum breeding performance in a humid tropical environment.…”
Section: Introductionmentioning
confidence: 99%
“…Most of this evidence was obtained from studies on temperate breeds of poultry raised in temperate environments. The same poultry breeds grown in tropical environments do not grow as fast as they do in temperate climates and have different nutrient requirements in the tropics (Babatunde and Fetuga, 1975;Olomu, 1976;Ogunmodede, 1977).…”
Section: Introductionmentioning
confidence: 98%
“…KISR1226, Kuwait. protein, and Nesheim et al (1972) concluded that excessive levels of some amino acids in the diet may increase the degradation rate of other amino acids, thus increasing the chick's need for them. Ogunmodede (1977) reported that the growth rate of broiler chicks tends to be lower in the tropics than in the temperate zone, which could be attributed to inadequate levels of essential amino acids or vitamins.…”
Section: Introductionmentioning
confidence: 96%